2001
DOI: 10.1055/s-2001-18549
|View full text |Cite
|
Sign up to set email alerts
|

Total Colectomy and Straight Ileo-Anal Soave Endorectal Pull-Through: Personal Experience with 42 Cases

Abstract: During the period from 1974 to June 2000 we used the straight ileo-anal Soave pull-through to treat 42 patients (24 affected by total colonic aganglionosis [TCA], 10 with ulcerative colitis and 8 with familial polyposis). The aim of this paper is to show that this operation, associated with total colectomy, is highly recommended, causing a lower number of complications when compared to the various "reservoir" techniques. The mean age of the 24 patients with TCA at the time of the pull-through was 2.8 years; in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
(13 reference statements)
2
9
0
Order By: Relevance
“…No case of stenosis or persistent constipation was seen and the proportion of patients with postoperative enterocolitis was not higher than in other series [14,32]. As regards to the straight ileo-anal pull-through, we share the opinion of other authors regarding its relative simplicity, its feasibility at a young age and the surprising adaptation of patients to the increased fecal volume along the years [8]. A comparison between both techniques was not possible because they were not performed during the same period and patients operated upon with straight pull-through are obviously younger than those operated on with the modified Martin.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…No case of stenosis or persistent constipation was seen and the proportion of patients with postoperative enterocolitis was not higher than in other series [14,32]. As regards to the straight ileo-anal pull-through, we share the opinion of other authors regarding its relative simplicity, its feasibility at a young age and the surprising adaptation of patients to the increased fecal volume along the years [8]. A comparison between both techniques was not possible because they were not performed during the same period and patients operated upon with straight pull-through are obviously younger than those operated on with the modified Martin.…”
supporting
confidence: 59%
“…Total colonic aganglionosis (TCA) accounts for 5 to 10 % of all cases of Hirschsprung's disease (HD) [15] and deserves separate consideration, because the nature of the operations aimed at reestablishing fecal flow through a healthy intestine may compromise nutrition, continence and quality of life (QOL). A long-term assessment of large cohorts of patients with TCA has seldom been made and reported results have been quite uneven, due in part to the inclusion in some series of patients with extensive small bowel or total intestinal aganglionosis [8,10,12,19,21,31,32]. Only a few specifically address QOL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an accumulation time of 1 year has proved to be good for the small bowel, and the time should be used for the patients treatment by means of suitable diet and medication in order to form mushy or solid stools from the ileostoma which provides much better conditions for postoperative management. Whether Soaves pullthrough with a safer anastomosis may have a better outcome still remains open, since separating rectal mucosa from the thinned out colon wall brings other problems in its train (2,4). Dodero et al (3) reported on very good results in 42 patients (24 affected by total colonic aganglionosis) after ileonal anastomosis according to Soaves technique but the evaluation protocol should be prospective and standardised.…”
Section: Discussionmentioning
confidence: 99%
“…We prefer to delay the definitive reconstructive procedure until the child is 1 year of age after a leveling ileostomy during the neonatal period. Some prefer to delay the reconstruction until later in life, 33 whereas others perform a pull-through without a diversion procedure in the neonatal period. [34][35][36] Another option is to perform the definitive reconstruction at diagnosis but leave a protective ileostomy until the child is toilet-trained for urine and is willing to tolerate rectal irrigations.…”
Section: Rectosigmoid Hirschsprung Diseasementioning
confidence: 99%